Barriers to technology integration in teaching English as a second language among English educators in Pakistan - Taj Abbasi, Wajahat; Ainol Haryati, Ibrahim; Fatimah, Ali (Universiti Malaysia Pahang, 2021)
The integration of information and communication technology is becoming a must for todays’ English as a second language teaching. Of late, worldwide situations and proven effectiveness have made technology integration necessary for educators to move with the flow. However, technology integration for English as a second language teaching environment among English educators in Pakistan is questionable. Therefore, this study aims to find out the barriers English language educators face in integrating technology in their teaching environments in the country. The study employed a mixed-method research design to collect data via an online questionnaire and interview protocols. The samples consist of 39 tertiary-level Pakistani ESL educators who responded to the online survey, and eight were chosen as interviewees. The findings revealed the unavailability of technology resources and lack of computer knowledge and skills training as part of the educators’ professional development as the core barriers to the technology-integration teaching in the country. The study calls for rigorous development and implementation of technology-based facilities and resources from the local authorities to be made available for the educators to incorporate in their English language teaching environments. The research also advocates for more intensive upskilling technology-based training for the educators as part of their continuous professional development programmes.